Pecoten Tradisi Hajatan Pernikahan dengan Media Undangan Rokok Suku Madura Desa Pasak Piang, Kecamatan Sungai Ambawang, Kabupaten Kubu Raya - Masud Masud; Hasanah Hasanah; Donatianus BSE Praptantya (Universitas Tanjungpura, 2021)
This research purpose was to explain madurese people understanding on the pecoten invitation. Pecoten tradition was a form of tradition that is still practiced by Madurese, in Pasak Piang Village. This tradition is still believed to carry a message of symbolic to the recipient. Pecoten tradition contains the meaning of a call that it is obligatory for people who accept pecoten invitation to come and can contribute to fill many envelopes.This research used theory by Roland Barthes. Berthas theory used the terms of the process of denotation and connotation in the special meaning contained in a sign or picture. Connotation is associated with culture that is implied in the meaning contained therein. The researcher used the ethnographic method within qualitative approach. Data collection instruments used observation, interview and documentation. Research results indicated that pecoten tradition has its own meaning. In pecoten tradition, the expression of pecoten tradition was to convey information that they have been invited to attend, so people who have received an invitation are required to attend a wedding celebration.